2020
DOI: 10.1177/0739986319900029
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Changes Among Latino/a Immigrant Parental Acculturation and Extra-Familial Immigration-Related Stress

Abstract: Foreign-born Latino/a immigrants currently make up 12.9% of the total U.S. population. Latino/a immigrants continue to be exposed to widespread health and mental health care disparities. Scholarship focused on the needs of Latino/a immigrants continues to be characterized by multiple gaps. Latino/a immigrants and their families, particularly those with low family annual incomes, are exposed to multiple types of immigration-related stress. However, little is known about how immigration-related stress impacts co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…However, Coco depicted multiple subtle themes around U.S. immigration, politics, and policy (Attig, 2019). Research has noted that bicultural positionality can serve as a protective factor against some of the negative effects of discrimination and stress for Latinx immigrant families (Whitehead et al, 2020). This film offered Mexican-heritage participants a rich cultural representation with which to identify, critique, appreciate, and discuss how they see themselves, not only in the direct content of the film, but within these larger sociopolitical contexts.…”
Section: Discussionmentioning
confidence: 99%
“…However, Coco depicted multiple subtle themes around U.S. immigration, politics, and policy (Attig, 2019). Research has noted that bicultural positionality can serve as a protective factor against some of the negative effects of discrimination and stress for Latinx immigrant families (Whitehead et al, 2020). This film offered Mexican-heritage participants a rich cultural representation with which to identify, critique, appreciate, and discuss how they see themselves, not only in the direct content of the film, but within these larger sociopolitical contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Immigrants are often negatively stereotyped, and these stereotypes have negative consequences for their psychosocial well-being. Immigration-related stress has been connected with low family annual incomes (Whitehead et al, 2020). Crossman (2013) reported that a gap existed in low-income rates between immigrants and those born in Canada, and this gap has risen greatly over the past 30 years.…”
Section: Discussionmentioning
confidence: 99%
“…They found that those parents encountered many immigration-related stressors. Some of the stressors were hard to deal with, which might impact their capacity to have another child (Whitehead, Parra-Cardona, Wampler, Bowles, & Klein, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Racial and/or ethnic minority status further exacerbates consequences associated with poverty (Murray et al, 2021) that can negatively impact individuals and their families. Such consequences include overexposure to the criminal justice and child welfare systems, low levels of education and employment, stigma and discrimination, and documentation issues (i.e., irregular documentation status), and when these families do seek help, there is a lack of diverse and culturally sensitive providers (Lavner et al, 2018; Visvanathan et al, 2014; Whitehead et al, 2020). In this context, African American and Hispanics, the two largest minority groups in the U.S., are at risk of relationship distress and they report lower rates of relationship functioning (Kelly & Floyd, 2006; Owen et al, 2012; Whitehead et al, 2020; Williamson et al, 2016).…”
Section: Introductionmentioning
confidence: 99%